Ratlarda Laminektomi Sonrası Aşırı Epidural Fibrozis Gelişmesinde Nitrik Oksitin Etkileri: Bir Ön Çalışma - Aladag, M Arif; Turkoz, Yusuf; Sahna, Engin; Cengiz, Nureddin; Parlakpınar, Hakan; Cihan, O Faruk; Gul, Mehmet (İnönü Üniversitesi, 2016)
Amaç: Laminektomi ve/veya diskektomi sonrası, tüm önleyici işlemlere rağmen, hastaların bir alt grubunda aşırı epidural fibrozis gelişmektedir. Bizim hipotezimiz, laminektomi sonrası aşırı fibrosis gelişen hastalarda yara iyileşmesinin geç safhasında nitrik oksit NO üretiminin arjinaz tarafından inhibisyonunda bir defektin olduğu şeklindedir. Amacımız, bir hayvan laminektomi modelinde aşırı fibrozis gelişmesi üzerinde NO ve arjinaz’ın etkisini araştırmaktır. Gereç ve Yöntem: Bu çalışmada, 50 erkek wistar rat beş gruba ayrıldı; tümüne lomber laminektomi yapıldı. Laminektomi sonrası 3. ve 12. gün arasında, 1. gruba kontrol serum fizyolojik, 2. gruba; indüklenebilir nitrik oksit sentazı iNOS uyarmak üzere lipopolisakkarit LPS , 3. gruba LPS ve L-arginin NOS substratı , 4. gruba gliseril trinitrat NO donörü ve 5. gruba L-valine arjinaz inhibitörü intraperitonal olarak verildi. Sonuçlar: Hayvanların tümü 12. gün sakrifiye edildi ve hayvanların tümünde epidural fibrozis gross ve histolojik inceleme ile değerlendirildi. 2. grupta yara iyileşmesi ve fibrozis zayıf iken, 3'üncü grupta hafif derecede kompresyon yapan bir epidural fibrozis vardı. 4. ve 5'inci gruplarda ise ciddi derecede kompresyon yapan bir epidural fibrozis vardı. Tartışma: iNOS inhibe edilerek NO üretiminin azalması ve L-arjinin’in büyük oranda arjinaz tarafından kullanılması, yara iyileşmesinin geç dönemindeki tamir ve yenilenme işlemini etkileyen en önemli faktörler olduğu kanaatindeyiz

Aim: In spite of all preventive procedures, extensive epidural fibrosis following laminectomy or/and dissectomy still remains a major problem. We hypothesized that the patients, who suffered from extensive fibrosis, have a defect in inhibition of nitric oxide NO production that make increase in fibroblastic activity and collagen accumulation in healing wound. Aim of this study is to explore the effect of NO and arginase on extensive fibrosis in an animal model of laminectomy. Material and Method: 50 male wistar rats are divided in five groups; all of them were made laminectomy in lumbar spine. Between the 3rd and 12th days, we gave saline to the group1 control group , lipopolysaccharide LPS to the group 2 to induce inducible nitric oxide synthase iNOS , LPS plus L-arginine NOS substrate to the group 3, glyceryl trinitrate NO donor to the group 4 and L-valine an arginase inhibitor to the group 5 intraperitonally. Results: All of these animals were sacrificed on the 12th day after operation, and the epidural fibrosis of everyanimal was evaluated by gross observation and histological examinations. While in the group 2 wound healing and fibrosis was poor, in the group 3, there was mild degree epidural fibrosis, but epidural fibrosis was not compressive. In group 4 and 5 there were severe degree compressive extensive epidural fibrosis. Conclusion: It was concluded that the reduction of NO production by inhibiting iNOS and largely use of Larginine by arginase are the most important factors that affect the process of repair and remodeling in the late period of wound healing, therefore, the absence or insufficiency in the NOS inhibition or extremism in NO production during late period of the wound healing leads to extensive epidural fibrosis
The Effects of Nitric Oxide on Extensive Epidural Fibrosis After Laminectomy in Rats: A Preliminary Study